Pre-pandemic patterns in colorectal cancer mortality and Black-White inequities across the 30 most populous US cities - Bolouri, Maryam; Sayed, Nazia S.; Benjamins, Maureen R.; Munoz, Nicholas R.; Halterman, Tyler; Silva, Abigail (Frontiers in Epidemiology, 2025)
BackgroundColorectal cancer (CRC) is a leading cause of cancer deaths in the United States. While national CRC mortality rates have improved over time, this rate differs between non-Hispanic (nH) Black and nH White populations and by geography.MethodsThe 30 most populous cities in the US were analyzed using national vital statistics data. Numerators were obtained from death certificates of residents of these cities with CRC as the underlying cause of death. US Census data provided population-based denominators. We calculated Black:White rate ratios (RRs) and corresponding confidence intervals for the most recent time period studied (2017–2019) to assess racial inequities. We calculated average annual percent changes to evaluate CRC mortality trends from 2009–2019.ResultsCRC mortality rates statistically significantly decreased nationally and in 25 of the 30 cities. In most cities, nH Black populations experienced a greater decrease in CRC mortality over time than nH White populations. However, in 20 cities, the Black:White CRC mortality rate ratio was greater than 1 (ranging from 1.28 in New York to 2.68 in Washington, D.C.; p < 0.05), indicating persistent racial inequities. Between 2009 and 2019, six cities saw statistically significant decreases in racial inequities, two cities saw increases, and the remaining cities demonstrated persistent disparities.ConclusionsDespite improvements in CRC mortality, Black:White disparities persist. Structural racism may contribute to these disparities through differential access to care and risk factor exposure. Identifying geographic differences in Black:White CRC mortality may serve as a catalyst for local governments to implement place-based initiatives that reduce screening barriers and contribute to health equity.